CoFe DMC-coated PmPD composite catalytic material, preparation method and application thereof, and preparation method of alkylphenol polyether
Through the preparation of CoFe DMC@PmPD composite catalytic material, the problem of the induction time of bimetallic cyanide catalyst in the synthesis of alkylphenol polyethers was solved, and the induction time was significantly shortened and the production efficiency was improved, and the metal ions were reduced. Residual, suitable for industrial production.
Patent Information
- Application Number
- CN202411347199.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2044-09-25
AI Technical Summary
When synthesizing alkylphenol polyethers using bimetallic cyanide catalyst (DMC), the induction time is too long, resulting in cumbersome production operations and prolonged reaction cycles. The use of high temperature and high amount of catalysts will cause metal ion residues to affect product performance.
CoFe DMC@PmPD composite catalytic material is used to improve catalytic activity by controlling the ratio of Co2+ and Fe3+, the mixed solution injection speed and aging time, and coat polymepthylenediamine through free radical polymerization to improve the surface properties of the catalyst and promote alkyl. Reaction of polyphenol with epoxy hydrocarbons.
It significantly shortens the induction time of alkylphenol polyether, reduces production costs, improves reaction efficiency, and reduces metal ion residues, and improves product performance.
Smart Images

Figure BDA0005062533120000101 
Figure BDA0005062533120000111
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of alkylphenol polyether synthesis, and specifically relates to a CoFeDMC@PmPD composite catalytic material and a preparation method and application thereof, and a preparation method of an alkylphenol polyether. Background Art
[0002] Double metal cyanide catalyst (DMC) was first developed by General Tire & Rubber Company in the United States in the 1960s. It has an open metal organic framework (MOF) structure, and transition metal ions can exist in different oxidation states while maintaining a cubic structure. Therefore, it has excellent chemical stability and can be widely used in different fields, such as catalysis, gas or ion capture, batteries, pigments, biomedical detection, imaging, treatment and sensors. In particular, DMC has inherent catalytic advantages such as abundant metal active sites, high porosity, diverse structures and adjustable chemical composition, and is widely used as an efficient catalyst for the synthesis of polyethers by ring-opening polymerization of epoxides. Compared with the alkaline catalysts used in the traditional synthesis of polyethers by ring-opening polymerization of epoxides, DMC has the advantages of less dosage, high catalytic activity and no need for post-treatment. The obtained polyether has the characteristics of high molecular weight, low unsaturation, high average functionality and narrow molecular weight distribution.
[0003] In industry, the continuous feeding method is often used to prepare polyethers with DMC. After propylene oxide or propylene oxide / ethylene oxide mixture is introduced, there is an induction period in the reaction. When the pressure drops suddenly and the temperature rises at the same time, it means that the induction is completed. After activation, the reaction will proceed stably. In particular, when synthesizing alkylphenol polyethers, due to the steric effect of the benzene ring and the carbon chain in the initiator structure, the hydroxyl group of alkylphenol and the alkylene oxide and DMC are difficult to interact with each other, resulting in a long induction time (greater than 4min) and even frequent induction failures. This is a common problem in the production of alkylphenol polyethers synthesized with DMC. The long induction period brings cumbersome production operations on the one hand and prolongs the reaction cycle on the other hand. Studies have found that when the reaction temperature rises or the amount of DMC increases, the induction period of synthesizing alkylphenol polyethers will be shortened. However, excessively high temperatures are bound to increase certain process risks and energy consumption in production operations, and a high amount of catalysts will cause metal ion residues in the finished polyethers. These metal ion residues can cause degradation of the polyethers on the one hand and affect the downstream application performance of the polyethers. Summary of the invention
[0004] The purpose of the present invention is to provide a CoFeDMC@PmPD composite catalytic material and a preparation method and application thereof, and a preparation method of an alkylphenol polyether. The CoFeDMC@PmPD composite catalytic material provided by the present invention can significantly shorten the synthesis induction time of the alkylphenol polyether, has a guiding significance for significantly reducing costs and increasing efficiency for the industrial production of the alkylphenol polyether, and is suitable for popularization and application.
[0005] In order to achieve the above object, the present invention provides the following technical solutions:
[0006] The present invention provides a method for preparing a CoFe DMC@PmPD composite catalytic material, comprising the following steps:
[0007] Mixing a water-soluble cobalt salt, a first citrate and water to obtain a cobalt salt mixed solution; the molar amounts of the water-soluble cobalt salt and the first citrate are equal;
[0008] Mixing hexacyanoferrate (III), a second citrate and water to obtain a hexacyanoferrate (III) mixed solution; the molar amounts of the hexacyanoferrate (III) and the second citrate are equal, and the molar ratio of the water-soluble cobalt salt to the hexacyanoferrate (III) is (0.1-0.5):(0.1-0.5);
[0009] The hexacyanoferrate (III) mixed solution is injected into the cobalt salt mixed solution, mixed and aged to obtain a CoFe DMC material; the injection speed is ≥100 μL·min -1 , aging time ≥ 24h;
[0010] The CoFe DMC material, meta-phenylenediamine, a free radical initiator and water are mixed, and a free radical polymerization reaction is carried out on the surface of the CoFe DMC material to obtain poly-meta-phenylenediamine, thereby obtaining a CoFe DMC@PmPD composite catalytic material.
[0011] Preferably, in the cobalt salt mixed solution: the volume ratio of the water-soluble cobalt salt to the water is (0.1-0.5) mmol: 25 mL;
[0012] In the hexacyanoferrate (III) mixed solution: the volume ratio of the molar amount of the hexacyanoferrate (III) to the water is (0.1-0.5) mmol: 25 mL;
[0013] The injection speed is 100-1000 μL·min -1 .
[0014] Preferably, the mass ratio of the CoFe DMC material to m-phenylenediamine is (10-100): (5-50);
[0015] The free radical initiator is ammonium persulfate, and the mass ratio of the CoFe DMC material to the free radical initiator is 1:1-2;
[0016] The free radical polymerization reaction is carried out in an ice water bath, and the free radical polymerization reaction time is 5 to 8 hours;
[0017] After the free radical polymerization reaction, a polymerization reaction liquid is directly obtained. After obtaining the polymerization reaction liquid, the method further comprises: separating the polymerization reaction liquid into solid and liquid, washing the obtained solid phase product and then drying it to obtain the CoFe DMC@PmPD composite catalytic material; the drying is vacuum drying, and the temperature of the vacuum drying is 50-100°C.
[0018] Preferably, an aged liquid is directly obtained after the aging, and after obtaining the aged liquid, the method further comprises: separating the aged liquid into solid and liquid, washing the obtained solid phase product and drying it to obtain the CoFe DMC material; the drying is vacuum drying, and the vacuum drying temperature is 50-100°C.
[0019] The present invention provides a CoFe DMC@PmPD composite catalytic material prepared by the preparation method described in the above technical scheme.
[0020] The present invention provides the use of the CoFe DMC@PmPD composite catalytic material described in the above technical solution in the preparation of alkylphenol polyether.
[0021] The present invention provides a method for preparing an alkylphenol polyether, comprising the following steps:
[0022] Alkylphenol, the CoFe DMC@PmPD composite catalytic material described in the above technical solution and olefin oxide are mixed, induced to activate and then heat-insulated to react to obtain alkylphenol polyether.
[0023] Preferably, the alkylphenol includes one or more of propylphenol, butylphenol, pentylphenol, heptylphenol, octylphenol, nonylphenol and decylphenol;
[0024] The oxidized olefins include propylene oxide or a mixture of ethylene oxide and propylene oxide;
[0025] When the oxidized olefin is a mixture of ethylene oxide and propylene oxide, the mass of the ethylene oxide accounts for 0 to 30% of the total mass of the mixture of ethylene oxide and propylene oxide, and is not zero.
[0026] Preferably, the number average molecular weight of the alkylphenol polyether is 500 to 1500;
[0027] The mass of the CoFe DMC@PmPD composite catalytic material accounts for 10 to 100 ppm of the total mass of the alkylphenol and the olefin oxide.
[0028] Preferably, the temperature of the heat preservation reaction is 130-160°C.
[0029] The invention provides a preparation method of a CoFe DMC@PmPD composite catalytic material, comprising the following steps: mixing a water-soluble cobalt salt, a first citrate and water to obtain a cobalt salt mixed solution; the molar amounts of the water-soluble cobalt salt and the first citrate are equal; mixing hexacyanoferrate (III) salt, a second citrate and water to obtain a hexacyanoferrate (III) salt mixed solution; the molar amounts of the hexacyanoferrate (III) salt and the second citrate are equal, and the molar ratio of the water-soluble cobalt salt to the hexacyanoferrate (III) salt is (0.1-0.5): (0.1-0.5); injecting the hexacyanoferrate (III) salt mixed solution into the cobalt salt mixed solution, mixing and aging, to obtain a CoFe DMC material; the injection speed is ≥100 μL·min -1 , aging time ≥ 24h; mixing the CoFe DMC material, m-phenylenediamine, a free radical initiator and water, and performing a free radical polymerization reaction on the surface of the CoFeDMC material to obtain polym-phenylenediamine, thereby obtaining a CoFe DMC@PmPD composite catalytic material. 2+ and Fe 3+ Two transition metal ions, while controlling the dosage ratio of raw materials during the preparation of CoFe DMC, the injection speed of the raw material solution during mixing, and the aging time, realize the control of the particle size, morphology, and surface state of CoFe DMC, thereby improving the catalytic activity of CoFe DMC and shortening the induction time of the catalyst; finally, the present invention coats poly(m-phenylenediamine) on the surface of CoFe DMC material by free radical polymerization reaction, and performs surface modification on the CoFe DMC core by poly(m-phenylenediamine) (PmPD), and utilizes the adhesion of poly(m-phenylenediamine) and its amino, acyl, and hydroxyl functional group characteristics to help the hydroxyl groups of alkylphenols and alkylene oxides, CoFe DMC, and interact with each other, thereby improving the reaction activity of CoFe DMC catalytic polyether synthesis, shortening the induction time, and achieving the effect of reducing costs and increasing efficiency. The results of the embodiment show that the CoFe DMC@PmPD composite catalytic material prepared by the present invention prepares alkylphenol polyether, and the induction time can be shortened by more than half, which has obvious guiding significance for reducing costs and increasing efficiency in the industrial production of alkylphenol polyether products. DETAILED DESCRIPTION
[0030] The present invention provides a method for preparing a CoFe DMC@PmPD composite catalytic material, comprising the following steps:
[0031] Mixing a water-soluble cobalt salt, a first citrate and water to obtain a cobalt salt mixed solution; the molar amounts of the water-soluble cobalt salt and the first citrate are equal;
[0032] Mixing hexacyanoferrate (III), a second citrate and water to obtain a hexacyanoferrate (III) mixed solution; the molar amounts of the hexacyanoferrate (III) and the second citrate are equal, and the molar ratio of the water-soluble cobalt salt to the hexacyanoferrate (III) is (0.1-0.5):(0.1-0.5);
[0033] The hexacyanoferrate (III) mixed solution is injected into the cobalt salt mixed solution, mixed and aged to obtain a CoFe DMC material; the injection speed is ≥100 μL·min -1 , aging time ≥ 24h;
[0034] The CoFe DMC material, meta-phenylenediamine, a free radical initiator and water are mixed, and a free radical polymerization reaction is carried out on the surface of the CoFe DMC material to obtain poly-meta-phenylenediamine, thereby obtaining a CoFe DMC@PmPD composite catalytic material.
[0035] In the present invention, unless otherwise specified, all preparation raw materials / components are commercially available products well known to those skilled in the art.
[0036] The present invention mixes a water-soluble cobalt salt, a first citrate and water (hereinafter referred to as the first water) to obtain a cobalt salt mixed solution; the molar amounts of the water-soluble cobalt salt and the first citrate are equal. In the present invention, the water-soluble cobalt salt is preferably cobalt nitrate, and specifically preferably Co(NO3)2·6H2O. The first citrate is preferably an alkali metal citrate, and specifically preferably sodium citrate and / or potassium citrate. The first water is preferably deionized water. In the cobalt salt mixed solution: the volume ratio of the molar amount of the water-soluble cobalt salt to the first water is preferably (0.1-0.5) mmol: 25 mL, more preferably (0.2-0.5) mmol: 25 mL, and specifically preferably 0.25 mmol: 25 mL, 0.4 mmol: 25 mL or 0.5 mmol: 25 mL. In the present invention, the amount of the first water cannot be too small. If the amount of the first water is too high, the molar concentration of the water-soluble cobalt salt will be too high, which will affect the catalytic performance of the target CoFe DMC@PmPD composite catalytic material.
[0037] The present invention mixes hexacyanoferrate (III), a second citrate and water (hereinafter referred to as the second water) to obtain a hexacyanoferrate (III) mixed solution; the molar amounts of the hexacyanoferrate (III) and the second citrate are equal, and the molar ratio of the water-soluble cobalt salt to the hexacyanoferrate (III) is (0.1-0.5): (0.1-0.5). In the present invention, the hexacyanoferrate (III) is preferably K3[Fe(CN)6]. The second citrate is preferably an alkali metal citrate, and is preferably sodium citrate and / or potassium citrate. The second water is preferably deionized water. The molar ratio of the water-soluble cobalt salt to the hexacyanoferrate (III) is preferably 1:1. In the present invention, in the hexacyanoferrate (III) mixed solution: the volume ratio of the molar amount of the hexacyanoferrate (III) to the second water is preferably (0.1-0.5) mmol: 25 mL, more preferably (0.2-0.5) mmol: 25 mL, and specifically preferably 0.25 mmol: 25 mL, 0.4 mmol: 25 mL or 0.5 mmol: 25 mL. In the present invention, the amount of the second water cannot be too small. If the amount of the second water is too small, the molar concentration of the hexacyanoferrate (III) will be too high, which will affect the catalytic performance of the target CoFe DMC@PmPD composite catalytic material.
[0038] After obtaining the hexacyanoferrate (III) mixed solution and the cobalt salt mixed solution, the present invention injects the hexacyanoferrate (III) mixed solution into the cobalt salt mixed solution, mixes and ages, and obtains the CoFe DMC material; the injection speed is ≥100 μL·min -1 , the aging time is ≥ 24h. In the present invention, the injection is preferably carried out at room temperature, specifically preferably at 25°C, and the injection is preferably carried out using a peristaltic pump. The injection speed is preferably 100 to 1000 μL·min -1 , more preferably 200 to 1000 μL·min -1 , preferably 300 μL·min -1 、800μL·min -1 or 1000 μL·min -1 The mixing is performed under stirring conditions, and the mixing time after the injection is preferably 1 to 2 hours. The aging time is preferably 24 to 30 hours, and more preferably 25 hours, 27 hours or 28 hours.
[0039] In the present invention, an aged liquid is directly obtained after the aging. After obtaining the aged liquid, the present invention preferably further comprises: separating the aged liquid into solid and liquid, washing the obtained solid phase product and drying it to obtain the CoFe DMC material. The solid-liquid separation is preferably centrifugation. The washing preferably comprises washing with deionized water and washing with ethanol in sequence. The specific implementation of the deionized water washing is preferably centrifugation, and the number of washings is preferably 2 times. The specific implementation of the ethanol washing is preferably centrifugation, and the number of washings is preferably 2 times. The drying is vacuum drying, and the temperature of the vacuum drying is preferably 50 to 100°C, and specifically preferably 60°C, 75°C or 90°C.
[0040] After obtaining the CoFe DMC material, the present invention mixes the CoFe DMC material, meta-phenylenediamine, a free radical initiator and water (hereinafter referred to as the third water), performs a free radical polymerization reaction on the surface of the CoFe DMC material to obtain poly-meta-phenylenediamine, and obtains a CoFe DMC@PmPD composite catalytic material. In the present invention, the mass ratio of the CoFe DMC material and meta-phenylenediamine is preferably (10-100): (5-50), and more preferably 2:1. The free radical initiator is preferably ammonium persulfate, and the mass ratio of the CoFe DMC material and the free radical initiator is preferably 1:1-2, and more preferably 1:1. The third water is preferably deionized water. The present invention has no special requirements for the amount of the third water, as long as the free radical polymerization reaction is smoothly carried out. In the present invention, the step of mixing the CoFe DMC material, m-phenylenediamine, a free radical initiator and the third water preferably comprises: ultrasonically dispersing the CoFe DMC material in the third water to obtain a CoFe DMC material dispersion; mixing the CoFe DMC material dispersion with the m-phenylenediamine and the free radical initiator. The ultrasonic dispersion is carried out under ice-water bath conditions. The ultrasonic dispersion time is preferably 20 to 30 minutes. The free radical polymerization reaction is preferably carried out under ice-water bath conditions, and the free radical polymerization reaction time is preferably 5 to 8 hours; the free radical polymerization reaction is carried out under stirring conditions. After the free radical polymerization reaction, a polymerization reaction liquid is directly obtained. After obtaining the polymerization reaction liquid, the present invention preferably further comprises: solid-liquid separation of the polymerization reaction liquid, washing the obtained solid phase product and drying it to obtain the CoFe DMC@PmPD composite catalytic material. The solid-liquid separation is preferably centrifugation. The washing preferably comprises washing with deionized water and washing with ethanol in sequence. The specific implementation of the deionized water washing is preferably centrifugation, and the number of washings is preferably 2 times. The specific implementation of the ethanol washing is preferably centrifugation, and the number of washings is preferably 2 times. The drying is vacuum drying, and the temperature of the vacuum drying is preferably 50-100°C, specifically preferably 60°C, 80°C or 100°C.
[0041] The present invention provides a CoFe DMC@PmPD composite catalytic material prepared by the preparation method described in the above technical scheme.
[0042] The present invention provides the use of the CoFe DMC@PmPD composite catalytic material described in the above technical solution in the preparation of alkylphenol polyether.
[0043] The present invention provides a method for preparing an alkylphenol polyether, comprising the following steps:
[0044] Alkylphenol, the CoFe DMC@PmPD composite catalytic material described in the above technical solution and olefin oxide are mixed, induced to activate and then heat-insulated to react to obtain alkylphenol polyether.
[0045] In the present invention, the alkylphenol preferably includes one or more of propylphenol, butylphenol, pentylphenol, heptylphenol, octylphenol, nonylphenol and decylphenol. The oxidized olefin preferably includes propylene oxide or a mixture of ethylene oxide and propylene oxide. When the oxidized olefin is a mixture of ethylene oxide and propylene oxide, the mass of the ethylene oxide preferably accounts for 0 to 30% of the total mass of the mixture of ethylene oxide and propylene oxide, and is not 0, and is more preferably 25%. The amount relationship of the alkylphenol and the oxidized olefin is based on the molecular weight of the alkylphenol polyether. The mass of the CoFe DMC@PmPD composite catalytic material preferably accounts for 10 to 100 ppm of the mass of the alkylphenol polyether, preferably 30 to 10 ppm, and specifically preferably 30 ppm, 50 ppm or 80 ppm. The number average molecular weight of the alkylphenol polyether is preferably 500 to 1500, and specifically preferably 800, 916, 1000 or 1200.
[0046] In the present invention, before the alkylphenol, the CoFe DMC@PmPD composite catalytic material described in the above technical solution and the oxidized olefin are mixed, the present invention preferably pre-dehydrates the alkylphenol. The pre-dehydration treatment is carried out in a reactor, and the temperature of the pre-dehydration treatment is preferably 115-120°C, and the vacuum degree is preferably ≥-0.095MPa. After the alkylphenol is pre-dehydrated, the present invention mixes the pre-dehydrated alkylphenol with the CoFe DMC@PmPD composite catalytic material, heats the temperature to the temperature of the insulation reaction, and then adds the oxidized olefin to directly enter the induction activation stage. The time of the induction activation is preferably 1-5 minutes, and specifically preferably 1 minute 33 seconds, 3 minutes 19 seconds, 4 minutes 20 seconds, and 3 minutes 40 seconds. The temperature of the insulation reaction is preferably 130-160°C, and more preferably 130-135°C, 140-145°C, 130-140°C or 155-160°C. After the reaction is completed, the alkylphenol polyether is obtained by degassing and discharging.
[0047] In order to further illustrate the present invention, the technical solutions provided by the present invention are described in detail below in conjunction with embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0048] Example 1
[0049] First, 0.25 mmol of Co(NO3)2·6H2O and an equal molar amount of sodium citrate were dissolved in 25 mL of deionized water to obtain solution A. 0.25 mmol of K3[Fe(CN)6] and an equal molar amount of sodium citrate were dissolved in 25 mL of deionized water to obtain solution B.
[0050] Then, in a 25°C water bath, a peristaltic pump was used to pump the mixture at a rate of 300 μL min -1 Solution B was added to solution A at a speed of 100 μg / min and the mixture was stirred for 1 h, wherein the molar amounts of Co(NO3)2·6H2O and K3[Fe(CN)6] were equal, both 0.25 mmol. After the mixture was aged for 25 h, the mixture was centrifuged and the precipitate was washed twice with deionized water and ethanol. Finally, the CoFe DMC catalyst was dried in a vacuum oven at 60°C.
[0051] 50 mg of CoFe DMC was dispersed in 100 mL of deionized water and ultrasonicated in ice water for 20 min. Then 25 mg of m-phenylenediamine and 50 mg of ammonium persulfate were added. The mixture was stirred in an ice water bath for 5 h, then centrifuged, and the precipitate was centrifuged and washed twice with deionized water and ethanol, and finally dried in a vacuum drying oven at 60 ° C to obtain the CoFe DMC@PmPD / A composite catalyst.
[0052] Example 2
[0053] First, 0.4 mmol of Co(NO3)2·6H2O and an equal molar amount of sodium citrate were dissolved in 25 mL of deionized water to obtain solution A. 0.4 mmol of K3[Fe(CN)6] and an equal molar amount of potassium citrate were dissolved in 25 mL of deionized water to obtain solution B.
[0054] The reaction was then placed in a 25°C water bath and the mixture was stirred at 800 μL min using a peristaltic pump. -1 Solution B was added to solution A at a speed of 100 μg / min and the mixture was stirred for 1 h. The molar amounts of Co(NO3)2·6H2O and K3[Fe(CN)6] were equal, both 0.4 mmol. After the mixture was aged for 28 h, the mixture was centrifuged and the precipitate was washed twice with deionized water and ethanol. Finally, the CoFe DMC catalyst was dried in a vacuum oven at 75°C.
[0055] 80 mg of CoFe DMC was dispersed in 100 mL of deionized water and ultrasonicated in ice water for 20 min. Then 40 mg of m-phenylenediamine and 80 mg of ammonium persulfate were added. The mixture was stirred in an ice water bath for 5 h, then centrifuged, and the precipitate was washed twice with deionized water and ethanol, and finally dried in a vacuum drying oven at 80 ° C to obtain the CoFe DMC@PmPD / B composite catalyst.
[0056] Example 3
[0057] First, 0.5 mmol of Co(NO3)2·6H2O and an equal molar amount of sodium citrate were dissolved in 25 mL of deionized water to obtain solution A. 0.5 mmol of K3[Fe(CN)6] and an equal molar amount of potassium citrate were dissolved in 25 mL of deionized water to obtain solution B.
[0058] The reaction was then placed in a 25°C water bath and the mixture was pumped at 1000 μL min -1 Solution B was added to solution A at a speed of 100 μg / min and the mixture was stirred for 1 h, wherein the molar amounts of Co(NO3)2·6H2O and K3[Fe(CN)6] were equal, both 0.5 mmol. After the mixture was aged for 27 h, the mixture was centrifuged and the precipitate was washed twice with deionized water and ethanol. Finally, the CoFe DMC catalyst was dried in a vacuum oven at 90°C.
[0059] 98 mg of CoFe DMC was dispersed in 100 mL of deionized water and ultrasonicated in ice water for 20 min. Then 49 mg of m-phenylenediamine and 98 mg of ammonium persulfate were added. The mixture was stirred in an ice water bath for 5 h, then centrifuged, and the precipitate was centrifuged and washed twice with deionized water and ethanol, and finally dried in a vacuum drying oven at 100 ° C to obtain the CoFe DMC@PmPD / C composite catalyst.
[0060] Comparative Example 1
[0061] The preparation method is basically the same as that of Example 2, except that the molar mass of Co(NO3)2·6H2O and K3[Fe(CN)6] is 1 mmol, the molar amount of Co(NO3)2·6H2O and sodium citrate in solution A is equal, the molar amount of K3[Fe(CN)6] and sodium citrate in solution B is equal, and the amount of deionized water in solution A and solution B is still 25 mL. The CoFe DMC@PmPD / D composite catalyst is obtained.
[0062] The preparation method is basically the same as that in Example 3, except that the peristaltic pump feed rate is 50 μL min -1 , and obtained the CoFe DMC@PmPD / E composite catalyst.
[0063] The preparation method is basically the same as that in Example 1, except that the aging time is shortened to 5 h to obtain a CoFeDMC@PmPD / F composite catalyst.
[0064] Example 4
[0065] 301g of propylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 1.5h at 115-120℃ and vacuum degree ≥-0.096MPa, then 0.162g of CoFe DMC@PmPD / A composite catalyst was added, and 1726g of propylene oxide was continuously added after the temperature was raised to 135℃, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 130-135℃. After the reaction was completed, the propylphenol polyether with a theoretical molecular weight of 916 was obtained by degassing and discharging. The induction time of the reaction was 1 minute and 33 seconds.
[0066] Example 5
[0067] 233g of heptylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 2h at 115-120℃ and vacuum degree ≥-0.096MPa, then 0.073g of CoFe DMC@PmPD / B composite catalyst was added, and 1223g of propylene oxide was continuously added after the temperature was raised to 140℃, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 140-145℃. After the reaction was completed, the heptylphenol polyether with a theoretical molecular weight of 1200 was obtained by degassing and discharging. The reaction induction time was 3 minutes and 19 seconds.
[0068] Example 6
[0069] 358g of octylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 1h at 115-120℃ and vacuum degree ≥-0.096MPa, then 0.042g of CoFe DMC@PmPD / C composite catalyst was added, and 1032g of propylene oxide was continuously added after the temperature was raised to 130℃, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 130-140℃. After the reaction was completed, the octylphenol polyether with a theoretical molecular weight of 800 was obtained by degassing and discharging. The reaction induction time was 4 minutes and 20 seconds.
[0070] Example 7
[0071] 432g of nonylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 1.5h at 115-120℃ and vacuum degree ≥-0.096MPa, then 0.157g of CoFe DMC@PmPD / A composite catalyst was added, and after heating to 138℃, 383g of ethylene oxide and 1148g of propylene oxide mixed olefins were continuously added, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 155-160℃. After the reaction was completed, the nonylphenol polyether with a theoretical molecular weight of 1000 was obtained by degassing and discharging. The reaction induction time was 3 minutes and 40 seconds.
[0072] Comparative Example 2
[0073] 301g of propylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 1.5h at 115-120°C and vacuum degree ≥-0.096MPa, then 0.162g of CoFe DMC catalyst (CoFe DMC catalyst prepared in Example 1) was added, and 1726g of propylene oxide was continuously added after the temperature was raised to 135°C, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 130-135°C. After the reaction was completed, the propylphenol polyether with a theoretical molecular weight of 916 was obtained by degassing and discharging. The reaction induction time was 4 minutes and 53 seconds.
[0074] Comparative Example 3
[0075] 233g of heptylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 2h at 115-120℃ and vacuum degree ≥-0.096MPa, then 0.073g of CoFe DMC@PmPD / D composite catalyst was added, and 1223g of propylene oxide was continuously added after the temperature was raised to 140℃, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 140-145℃. After the reaction was completed, the heptylphenol polyether with a theoretical molecular weight of 1200 was obtained by degassing and discharging. The reaction induction time was 6 minutes and 46 seconds.
[0076] Comparative Example 4
[0077] 358g of octylphenol was added to a 2.5L polymerization reactor, heated and stirred, dehydrated for 1h at 115-120°C and vacuum ≥-0.096MPa, then 0.042g of CoFe DMC@PmPD / E composite catalyst was added, and 1032g of propylene oxide was continuously added after the temperature was raised to 130°C, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 130-140°C. After the reaction was completed, the octylphenol polyether with a theoretical molecular weight of 800 was obtained by degassing and discharging. The reaction induction time was 10 minutes and 01 seconds.
[0078] Comparative Example 5
[0079] 432g of nonylphenol was added into a 2.5L polymerization reactor, heated and stirred, and dehydrated for 1.5h at 115-120°C and vacuum degree ≥-0.096MPa, then 0.157g of CoFe DMC@PmPD / F composite catalyst was added, and after heating to 138°C, 383g of ethylene oxide and 1148g of propylene oxide mixed olefins were continuously added, waiting for induced activation. Activation failed and there was no reaction.
[0080] Comparative Example 6
[0081] 432g of nonylphenol was added to a 2.5L polymerization reactor, heated and stirred, and dehydrated for 1.5h at 115-120°C and vacuum degree ≥-0.096MPa, then 0.157g of CoFe DMC catalyst (CoFe DMC catalyst prepared in Example 1) was added, and after heating to 138°C, 383g of ethylene oxide and 1148g of propylene oxide mixed olefins were continuously added, and the reaction was kept warm after induction activation, and the reaction temperature was maintained at 155-160°C. After the reaction was completed, the nonylphenol polyether with a theoretical molecular weight of 1000 was obtained by degassing and discharging. The reaction induction time was 9 minutes and 42 seconds.
[0082] Table 1 Summary of induction time of Examples 4 to 7 and Comparative Examples 2 to 6
[0083]
[0084]
[0085] As shown in Table 1, the results of Examples 4 to 7 and Comparative Examples 2 to 7 are analyzed:
[0086] In Example 4 and Comparative Example 2: In Example 4, the CoFe DMC@PmPD / A composite catalyst prepared in Example 1 was used to catalyze the reaction of propylphenol and propylene oxide to generate propylphenol polyether, and the reaction induction time was 1 minute and 33 seconds. Comparative Example 2 used the CoFe DMC catalyst prepared in Example 1 to catalyze the reaction of propylphenol and propylene oxide to generate propylphenol polyether, and the reaction induction time was 4 minutes and 53 seconds.
[0087] In Example 5 and Comparative Example 3: In Example 5, the CoFe DMC@PmPD / B composite catalyst prepared in Example 2 was used to catalyze the reaction of heptylphenol and propylene oxide to generate heptylphenol polyether, and the reaction induction time was 3 minutes and 19 seconds. In Comparative Example 3, the DMC@PmPD / D composite catalyst prepared in Comparative Example 1 was used to catalyze the reaction of heptylphenol and propylene oxide to generate heptylphenol polyether, and the reaction induction time was 6 minutes and 46 seconds.
[0088] In Example 6 and Comparative Example 4: Example 6 uses the CoFe DMC@PmPD / C composite catalyst prepared in Example 3 to catalyze the reaction of octylphenol and propylene oxide to generate octylphenol polyether, and the reaction induction time is 4 minutes and 20 seconds. Comparative Example 4 uses the CoFe DMC@PmPD / E composite catalyst prepared in Comparative Example 1 to catalyze the reaction of octylphenol and propylene oxide to generate octylphenol polyether, and the reaction induction time is 10 minutes and 01 seconds.
[0089] In Example 7 and Comparative Example 6: In Example 7, the CoFe DMC@PmPD / A composite catalyst prepared in Example 1 was used to catalyze the reaction of nonylphenol with a mixed olefin of ethylene oxide and propylene oxide to form nonylphenol polyether, and the reaction induction time was 3 minutes and 40 seconds. In Comparative Example 6, the CoFe DMC catalyst prepared in Example 1 was used to catalyze the reaction of nonylphenol with a mixed olefin of ethylene oxide and propylene oxide to form nonylphenol polyether, and the reaction induction time was 9 minutes and 42 seconds.
[0090] In Example 7 and Comparative Example 5: In Example 7, the CoFe DMC@PmPD / A composite catalyst prepared in Example 1 was used to catalyze the reaction of nonylphenol with a mixed olefin of ethylene oxide and propylene oxide to form nonylphenol polyether, and the reaction induction time was 3 minutes and 40 seconds. In Comparative Example 5, the CoFe DMC@PmPD / F prepared in Comparative Example 1 was used to catalyze the reaction of nonylphenol with a mixed olefin of ethylene oxide and propylene oxide, but the activation failed and no reaction occurred.
[0091] From the comparison results of Example 4 and Comparative Example 2 and the comparison results of Example 7 and Comparative Example 6, it can be seen that the induction time of preparing alkylphenol polyether using the CoFe DMC@PmPD composite catalyst is shortened compared with the original CoFe DMC catalyst for preparing alkylphenol polyether, which has an obvious advantage.
[0092] From the comparison results of Example 5 and Comparative Example 3, the comparison results of Example 6 and Comparative Example 4, and the comparison results of Example 7 and Comparative Example 5, it can be seen that after the operating conditions of the composite catalyst prepared in Comparative Example 1 are changed, the effect on the synthesis induction time of alkylphenol polyether is general, and the effect of shortening the induction time cannot be achieved, and even the reaction catalysis effect cannot be achieved.
[0093] In summary, compared with the alkylphenol polyether prepared directly with CoFe DMC under the same reaction conditions, the alkylphenol polyether prepared by the CoFe DMC@PmPD composite catalyst prepared by the present invention has a significantly shortened induction time (the induction time can be shortened by more than half). Therefore, the CoFe DMC@PmPD composite catalyst prepared by the present invention has obvious guiding significance for reducing costs and increasing efficiency in the industrial production of catalyzing alkylphenol to prepare alkylphenol polyether, and is suitable for popularization and use.
[0094] Although the above embodiment describes the present invention in detail, it is only a part of the embodiments of the present invention, not all of the embodiments. Other embodiments can be obtained based on this embodiment without creativity, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A method for preparing a CoFe DMC@PmPD composite catalytic material, characterized in that: The following steps are involved: Mixing a water-soluble cobalt salt, a first citrate and water to obtain a cobalt salt mixed solution; the molar amounts of the water-soluble cobalt salt and the first citrate are equal; Mixing hexacyanoferrate (III), a second citrate and water to obtain a hexacyanoferrate (III) mixed solution; the molar amounts of the hexacyanoferrate (III) and the second citrate are equal, and the molar ratio of the water-soluble cobalt salt to the hexacyanoferrate (III) is (0.1-0.5):(0.1-0.5); The hexacyanoferrate (III) mixed solution is injected into the cobalt salt mixed solution, mixed and aged to obtain a CoFeDMC material; the injection speed is ≥100 μL·min -1 , aging time ≥ 24h; The CoFe DMC material, meta-phenylenediamine, a free radical initiator and water are mixed, and a free radical polymerization reaction is carried out on the surface of the CoFe DMC material to obtain poly-meta-phenylenediamine, thereby obtaining a CoFe DMC@PmPD composite catalytic material.
2. The preparation method according to claim 1, characterized in that: In the cobalt salt mixed solution: the volume ratio of the water-soluble cobalt salt to the water is (0.1-0.5) mmol: 25 mL; In the hexacyanoferrate (III) mixed solution: the volume ratio of the molar amount of the hexacyanoferrate (III) to the water is (0.1-0.5) mmol: 25 mL; The injection speed is 100-1000 μL·min -1 .
3. The preparation method according to claim 1, characterized in that: The mass ratio of the CoFe DMC material to m-phenylenediamine is (10-100): (5-50); The free radical initiator is ammonium persulfate, and the mass ratio of the CoFe DMC material to the free radical initiator is 1:1-2; The free radical polymerization reaction is carried out in an ice water bath, and the free radical polymerization reaction time is 5 to 8 hours; After the free radical polymerization reaction, a polymerization reaction liquid is directly obtained. After obtaining the polymerization reaction liquid, the method further comprises: separating the polymerization reaction liquid into solid and liquid, washing the obtained solid phase product and then drying it to obtain the CoFe DMC@PmPD composite catalytic material; the drying is vacuum drying, and the temperature of the vacuum drying is 50-100°C.
4. The preparation method according to claim 1, characterized in that: After the aging, an aging liquid is directly obtained. After obtaining the aging liquid, the process further includes: separating the aging liquid into solid and liquid, washing the obtained solid phase product and drying it to obtain the CoFeDMC material; the drying is vacuum drying, and the vacuum drying temperature is 50-100°C.
5. The CoFe DMC@PmPD composite catalytic material prepared by the preparation method according to any one of claims 1 to 4.
6. Use of the CoFe DMC@PmPD composite catalytic material according to claim 5 in the preparation of alkylphenol polyether.
7. A method for preparing an alkylphenol polyether, characterized in that: The following steps are involved: Alkylphenol, the CoFe DMC@PmPD composite catalytic material according to claim 5 and olefin oxide are mixed, induced to activate and then heat-insulated to react to obtain alkylphenol polyether.
8. The preparation method according to claim 7, characterized in that: The alkylphenol includes one or more of propylphenol, butylphenol, pentylphenol, heptylphenol, octylphenol, nonylphenol and decylphenol; The oxidized olefins include propylene oxide or a mixture of ethylene oxide and propylene oxide; When the oxidized olefin is a mixture of ethylene oxide and propylene oxide, the mass of the ethylene oxide accounts for 0 to 30% of the total mass of the mixture of ethylene oxide and propylene oxide, and is not zero.
9. The preparation method according to claim 7 or 8, characterized in that: The number average molecular weight of the alkylphenol polyether is 500 to 1500; The mass of the CoFe DMC@PmPD composite catalytic material accounts for 10 to 100 ppm of the total mass of the alkylphenol and the olefin oxide.
10. The preparation method according to claim 7, characterized in that: The temperature of the heat preservation reaction is 130-160°C.
Citation Information
Patent Citations
Method for synthesizing fatty alcohol polyether with wide molecular weight distribution by modifying double metal cyanide
CN116376001A
Metal hexacyanocobaltate nitroferricyanide complexes
CN1360609A